2022
DOI: 10.1159/000521147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Food Allergy among Schoolchildren in Lebanon

Abstract: <b><i>Introduction:</i></b> Food allergy (FA) is a global health problem with an ongoing rise in prevalence, especially in developed countries. It has been reported to be most prevalent in children, although cases in adults have been increasing as well. FA may lead to life-threatening clinical manifestations. Data in Lebanon and the Middle East are limited. To our knowledge, few studies tackled its prevalence in children in this region. <b><i>Aim:</i></b> This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“… 33 Another reason is that there are gender specific differences in food intolerances, whereby women have been shown to suffer more often from food related symptoms due to hormonal differences, intake of medications, etc. 24 As for the common food allergens, our results are similar to that of Irani et al, 18 who reported fruits, nuts, and spices to be among the top 5 most prevalent food allergies among self-reported food allergic individuals in Lebanon, and to that of Sakakini et al, 30 who reported fruits, vegetables, and nuts to be among the most common allergens among Lebanese school children. Regarding food allergy symptoms, similar results were found in studies conducted in Mauritius and Lebanon, which also classified cutaneous and gastrointestinal symptoms to be the most frequently reported food allergy symptoms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 33 Another reason is that there are gender specific differences in food intolerances, whereby women have been shown to suffer more often from food related symptoms due to hormonal differences, intake of medications, etc. 24 As for the common food allergens, our results are similar to that of Irani et al, 18 who reported fruits, nuts, and spices to be among the top 5 most prevalent food allergies among self-reported food allergic individuals in Lebanon, and to that of Sakakini et al, 30 who reported fruits, vegetables, and nuts to be among the most common allergens among Lebanese school children. Regarding food allergy symptoms, similar results were found in studies conducted in Mauritius and Lebanon, which also classified cutaneous and gastrointestinal symptoms to be the most frequently reported food allergy symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding food allergy symptoms, similar results were found in studies conducted in Mauritius and Lebanon, which also classified cutaneous and gastrointestinal symptoms to be the most frequently reported food allergy symptoms. 30 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Food allergy (FA) is a major public health issue globally, affecting about 8% of children and 10% of adults (see Fig 1 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 for global prevalence data). FA has a negative impact on the lives of patients with allergy and their families, and there is no curative treatment.…”
mentioning
confidence: 99%